Analisis Hukum terhadap Putusan Nomor 6234/Pdt.G/2020/ Pa. Badg Akibat Wanprestasi Nasabah pada Pembiayaan Murabahah - Rahmat Fizran; Mohamad Andri Ibrahim; Intan Manggala Wijayanti (UNISBA Press, 2023)
Abstract. Murabahah is an agreement to buy and sell an item by affirming its purchase price to the buyer and the buyer paying it at a higher price as an agreed profit. In murabahah financing, there are sometimes defaults, for example defaults committed by Bank Syariah Indonesia customers with case number 6234/Pdt.G/2020/ Pa. Badg. Customers in 2017 received murabahah financing, initially customers were able to fulfill their obligations, but at the beginning of 2019 customers could not fulfill their installments to the bank so the bank gave warnings one to three, but customers did not heed it. In addition, the bank had also offered restructuring, but it was rejected by the customer. Then it is appropriate for the bank to execute the bank's dependent rights as the first dependent rights holder to execute the dependent rights alone or through the KPKNL. The auction of this guarantee is considered to be detrimental to the customer because the price limit of the collateral object is too low and the execution of this auction should be carried out through the fiat of the local religious court, because this makes the customer or plaintiff sue the BSI bank to the religious court As for the judge's decision in this case is to reject the customer's lawsuit. the urgency of this study is to know the bank's handling of problematic murabahah financing in BSI and the legal analysis of the judgment number 6234/Pdt.G/2020/ Pa. Badg due to default of the client on the murbahah settlement. The methods used are qualitative, interview data collection techniques, literature studies and documentation. Data analysis techniques condense data, display data, and draw conclusions the results of this study show that the price limit determined by the bank without customer agreement does not conflict with the MUI fatwa of the National Shari'a Council No. 47 / DSN-MUI / II / 2005. Abstrak. Murabahah merupakan akad jual beli suatu barang dengan menegaskan harga belinya kepada pembeli dan pembeli membayarnya dengan harga yang lebih sebagai keuntungan yang disepakati. Dalam pembiayaan murabahah kadang terjadi wanprestasi, Sebagai contoh wanprestasi yang dilakukan oleh nasabah Bank Syariah Indonesia dengan nomor perkara 6234/Pdt.G/2020/ Pa. Badg. Nasabah ditahun 2017 mendapatkan pembiayaan murabahah, pada awalnya nasabah dapat memenuhi kewajibannya, akan tetapi diawal tahun 2019 nasabah tidak dapat memenuhi angsurannya kepada bank sehingga bank memberikan peringatan satu hingga tiga, tetapi nasabah tidak mengindahkannya. Selain itu bank juga sudah menawarkan restrukturisasi, tetapi ditolak oleh nasabah. Maka sudah selayakanya bank mengeksekusi hak tanggungan bank sebagai pemegang hak tanggungan pertama mengeksekusi hak tanggungan secara sendiri atau melalui KPKNL. Adapun pelelangan jaminan ini dirasa merugikan nasabah dikarenakan limit harga objek jaminan terlalu rendah dan seharusnya eksekusi lelang ini dilakukan melalui fiat pengadilan agama setempat, karena hal inilah membuat nasabah atau penggugat menggugat bank BSI ke pengadilan agama Adapun putusan hakim dalam perkara ini ialah menolak gugatan nasabah. urgensi penelitian ini adalah mengetahui penanganan bank terhadap pembiayaan murabahah bermasalah di BSI dan analisis hukum terhadap putusan nomor 6234/Pdt.G/2020/ Pa. Badg akibat wanprestasi nasabah pada pembiyaan murbahah. Metode yang digunakan ialah kualitatif, Teknik pengumpulan data wawancara, studi literatur dan dokumentasi. Teknik analisis data memadatkan data, menampilkan data, dan menarik kesimpulan hasil penelitian ini menunjukan bahwa limit harga yang ditentukan bank tanpa kesepakatan nasabah tidak bertentangan dengan fatwa MUI Dewan Syari’ah Nasional No 47/DSN-MUI/II/2005.